Literasi Keuangan Digital pada Kelompok Wanita Tani (KWT) di Desa Durian Demang Kabupaten Bengkulu Tengah - Agusti, Netta; Yuliarti, Ellys (Jurnal Pengabdian Kepada Masyarakat, 2025)
Adoption of digital financial services has the potential to empower women farmers and increase their financial inclusion. This community service provides simple digital financial literacy to women farmer groups (KWT) in Durian Demang Village through socialization, training, and introduction of the SiApik application. The training includes digital money management, online security, digital payments, savings, investments, loans, insurance, as well as fraud prevention and digital budgeting. Participants were enthusiastic because they actively managed household and group finances. However, the digital literacy gap is still a challenge. With the support of appropriate financial products and the right policies, simple digital finance can significantly improve the financial management skills of women farmers.